Small Caliber Compliant Vascular Grafts Based on Elastin-Like Recombinamers for in situ Tissue Engineering - Fernández-Colino, Alicia; Wolf, Frederic; Rütten, Stephan; Schmitz-Rode, Thomas; Rodríguez-Cabello, Jose Carlos; Jockenhoevel, Stefan; Mela, Petra (Frontiers in Bioengineering and Biotechnology, 2019)
Vascular disease is a leading cause of death worldwide, but surgical options are restricted by the limited availability of autologous vessels, and the suboptimal performance of prosthetic vascular grafts. This is especially evident for coronary artery by-pass grafts, whose small-caliber is associated with a high occlusion propensity. Despite the potential of tissue-engineered grafts, compliance mismatch, dilatation, thrombus formation and the lack of functional elastin are still major limitations leading to graft failure. This calls for advanced materials and fabrication schemes to achieve improved control on the grafts’ properties and performance. Here, bioinspired materials and technical textile components are combined to create biohybrid cell-free implants for endogenous tissue regeneration. Clickable elastin-like recombinamers are processed to form an open macroporous 3D architecture to favor cell ingrowth, while being endowed with the non-thrombogenicity and the elastic behavior of the native elastin. The textile components (i.e. warp-knitted and electrospun meshes) are designed to confer suture retention, long-term structural stability, burst strength and compliance. Notably, by controlling the electrospun layer’s thickness, the compliance can be modulated over a wide range of values encompassing those of native vessels. The grafts support cell ingrowth, extracellular matrix deposition and endothelium development in vitro. Overall, the fabrication strategy results in promising off-the-shelf hemocompatible vascular implants for in situ tissue engineering by addressing the known limitations of bioartificial vessel substitutes.